The Impact of Employee Well-being on Organizational Loyalty: The Mediating Role of Job Satisfaction An Applied Study on Telecommunications Companies in Jordan - Aliwaimer, Hijar Hussien; Alshibly, Haitham Hmoud (The Arab Journal of Administration, 2024)
This study aimed to identify the extent to which telecommunications companies in Jordan provide employee well-being practices and determine the best programs to enhance them. It also examined the impact of well-being on job satisfaction, organizational loyalty, and the mediating role of job satisfaction. This study was applied to employees working in Jordanian telecommunications companies in the capital Amman (Zain, Orange, Umniah). A field approach was used to collect data through a survey questionnaire distributed to 397 suitable samples of employees within the main branches of telecommunications companies in the capital Amman. The study used a descriptive analytical approach and statistical software to analyze the data. The findings showed that employee well-being practices, as indicated by their dimensions (psychological well-being, social well-being, workplace well-being), positively impact organizational loyalty. Psychological well-being strengthens loyalty through a supportive work environment that realizes employees’ full potential and promotes positive feelings at work. Social well-being enhances loyalty by encouraging teamwork. Workplace well-being builds loyalty by providing an enjoyable environment and healthy working conditions. Additionally, the study found that employee well-being practices, as indicated by their dimensions, increase job satisfaction in these companies. Job satisfaction partially mediates the relationship between employee well-being practices and organizational loyalty. The study concluded that integrating employee well-being initiatives into companies’ strategies and policies is necessary. Loyalty can be enhanced by applying these practices and satisfaction increased by providing compensation and incentives proportionate to employees’ efforts.